2017
DOI: 10.1093/cvr/cvx188
|View full text |Cite
|
Sign up to set email alerts
|

CXCL12-CXCR4 signalling plays an essential role in proper patterning of aortic arch and pulmonary arteries

Abstract: CXCL12-CXCR4 signalling is essential for the correct patterning of aortic arches and pulmonary arteries during development. Superfluous arteries in Cxcl12-null lungs and the aortic arch infer a role of CXCL12 in protecting arteries from uncontrolled sprouting during development of the arterial system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 53 publications
(67 reference statements)
3
24
0
Order By: Relevance
“…The interaction between SDF-1 and CXCR4 is essential for hematopoiesis (Karpova and Bonig, 2015). In addition, the SDF-1/CXCR4 axis has multiple essential roles in life (Murphy and Heusinkveld, 2018), such as embryonic (Mcgrath et al, 1999) and vascular (Takabatake et al, 2009;Kim et al, 2017) development, while providing support for the survival and migration of neoplastic cells (Chatterjee et al, 2014). The polymorphisms of SDF-1 might affect the ability to prevent HIV-1 infection (Winkler et al, 1998;Kuipers et al, 1999).…”
Section: The Biological Functions Of Hiv Coreceptorsmentioning
confidence: 99%
“…The interaction between SDF-1 and CXCR4 is essential for hematopoiesis (Karpova and Bonig, 2015). In addition, the SDF-1/CXCR4 axis has multiple essential roles in life (Murphy and Heusinkveld, 2018), such as embryonic (Mcgrath et al, 1999) and vascular (Takabatake et al, 2009;Kim et al, 2017) development, while providing support for the survival and migration of neoplastic cells (Chatterjee et al, 2014). The polymorphisms of SDF-1 might affect the ability to prevent HIV-1 infection (Winkler et al, 1998;Kuipers et al, 1999).…”
Section: The Biological Functions Of Hiv Coreceptorsmentioning
confidence: 99%
“…CXCL12-CXCR4 signaling is necessary for artery formation, as well as for the establishment of proper branching patterns and formation of connections between adjacent vessels. 11,15,17,18 Here, we observed that the stapedial artery is initially formed but then degenerates during later stages of development in Cxcl12 −/− embryos (Figures 2 and 3). Because NCC migration and condensation to form the stapes both occurred in the absence of CXCL12 signaling (Figure 2), it is possible that CXCL12 signaling promotes formation of the central foramen by maintaining the stapedial artery in the middle of the condensing mesenchyme, rather than by directly regulating NCC migration and stapes condensation.…”
Section: Cxcl12 Deficiency Results In the Loss Of The Stapedial Artmentioning
confidence: 62%
“…10 As such, in Cxcl12 null mice, the branching pattern of aortic arches and pulmonary arteries are severely disrupted. 11 In addition, CXCL12 signaling has been shown to regulate NCC migration, as well as the subsequent patterning and morphogenesis of NCC-derived cells and tissues. 9,12,13 Based on the essential roles of CXCL12 in NCC migration and angiogenesis and that the stapes is derived from NCCs and closely associated with a blood vessel, we hypothesized that CXCL12 signaling is also involved in normal stapes development.…”
Section: Introductionmentioning
confidence: 99%
“…Complex congenital cardiac malformations such as tetralogy of Fallot are much more common in WHIM patients than the general population . These have not been described in WHIM knock in mice; however, Cxcr4 knockout mice also have cardiovascular malformations, including ventricular septal defects and abnormal gastric vascular development . Further, patients with DiGeorge Syndrome, in which the thymus fails to develop, also commonly have defects of the aortic arch and altered CXCR4‐mediated migration of cardiac progenitor cells.…”
Section: Other Findingsmentioning
confidence: 99%
“…56 These have not been described in WHIM knock in mice; however, Cxcr4 knockout mice also have cardiovascular malformations, including ventricular septal defects and abnormal gastric vascular development. [57][58][59][60] Further, patients with DiGeorge Syndrome, in which the thymus fails to develop, also commonly have F I G U R E 5 Model of WHIM syndrome molecular and cellular immunopathogenesis. M, myelokathexis; H, hypogammaglobulinemia; I, infections; W, warts defects of the aortic arch and altered CXCR4-mediated migration of cardiac progenitor cells.…”
Section: Other Find Ing Smentioning
confidence: 99%